Effect of Mulching, Manures and chemical fertilizers on anatomical characters of (Solanum tuberosum L.) potato plants - Baghdad Science Journal (مجلة بغداد للعلوم, 2011)
Anatomy studies were carried out in the experimental field, College of Agriculture, University of Baghdad to have better understanding of the influence of mulching with black polyethylene sheets, organic manure and chemical fertilizer on the anatomy changes in potato shoot and leaves tissues. Results showed that leaves area, leaves area index and chlorophyll percentage were significantly increased by using mulching and chemical fertilizer by (7463.70 cm2, 3.97, 45.33 SPAD units) respectively. Also this treatment significantly increased total stomata number and in both lower and upper sides of the leaf by (957,721,176) stomata /mm2 respectively. But by using mulching treatment with organic manure significantly increased vessels and sieve tubes diameter by (12.5, 2.75) micron for respectively. However the control treatment significantly increased leaves thickness spongy mesophyll by (45) micron, while the palisade parenchyma thickness was significantly increased to 26.25 micron in mulching and chemical fertilizers treatment. In conclusion, the interaction between mulching with black polyethylene sheets and fertilizing with organic and chemical manure , caused same anatomy characteristic changes which increased the potatoes plant yield and the ability to drought tolerance.